2015
DOI: 10.3141/2481-09
|View full text |Cite
|
Sign up to set email alerts
|

Failure Probability of Resurfaced Preventive Maintenance Treatments

Abstract: This study evaluated the effectiveness of various pavement preventive maintenance treatments through investigation of the failure probability of different performance indicators, including roughness, alligator cracking, longitudinal cracking, transverse cracking, rutting, and friction. For the study, 354 resurfacing pavement preventive maintenance projects were collected from the Long-Term Pavement Performance program database, including ones that used thin asphalt overlay, chip seal, slurry seal, and fog seal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Investment in the construction and maintenance of transport infrastructure is enormous, and its repercussions can be seen in all areas of society (Hildén et al 2004). Regarding this, the road infrastructure supply for better mobility and transportation performance is generally used as an indicator and can be measured from four perspectives: state of the pavement, traffic capacity, safety, and accessibility (Alavi et al 2016, Dong, Huang 2015, Song et al 2020. In terms of interurban roads, the importance of roadways in the entire national infrastructure is evident.…”
Section: Development Of the Territorial Infrastructure Support Index ...mentioning
confidence: 99%
“…Investment in the construction and maintenance of transport infrastructure is enormous, and its repercussions can be seen in all areas of society (Hildén et al 2004). Regarding this, the road infrastructure supply for better mobility and transportation performance is generally used as an indicator and can be measured from four perspectives: state of the pavement, traffic capacity, safety, and accessibility (Alavi et al 2016, Dong, Huang 2015, Song et al 2020. In terms of interurban roads, the importance of roadways in the entire national infrastructure is evident.…”
Section: Development Of the Territorial Infrastructure Support Index ...mentioning
confidence: 99%
“…Therefore, this study employed the short-term pavement performance in terms of longitudinal cracking, transverse cracking, alligator cracking, roughness, and rutting as indicators to evaluate the effectiveness of the PM treatments. These research results have revealed that thin overlay is the most effective PM treatment, followed by chip seal, and slurry seal [2,11,19]. In contrast, crack seal does not have as good long-term effectiveness as the other PM treatments [2,20].…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies also employed general statistical methods, regression models, survival analysis, etc. to compare the effectiveness of the PM treatments on mitigating pavement distresses, and the results showed that the effectiveness of PM treatments varies on different pavement distresses [10][11][12]. Therefore, the effectiveness evaluation of different PM treatments on each kind of pavement distress would be needed to support decision-making in the selection of an appropriate PM treatment for a pavement distress.…”
Section: Introductionmentioning
confidence: 99%
“…LTPP database is worthy of the name of the largest pavement performance database, test sections from LTPP were used extensively in the calibration process, which can provide pavement engineers with historically recorded climate information, monitoring of distress and response, materials testing, maintenance, and especially pavement performance monitoring data. LTPP data were employed to conduct local and national calibration of the pavement performance by many researchers on both in-service flexible and rigid pavements [4][5][6][7], as well as survival analysis for preventive maintenance [8,9]. However, as mentioned by Prozzi and Madanat [10], the pavement distress is an event of high variety, and it was more reasonable to describe the failure of pavement by a function of probability density rather than by a fixed-point estimation.…”
Section: Introductionmentioning
confidence: 99%